1984
DOI: 10.1007/bf02406136
|View full text |Cite
|
Sign up to set email alerts
|

Tensile forces enhance prostaglandin E synthesis in osteoblastic cells grown on collagen ribbons

Abstract: An experimental system has been developed to examine the prostaglandin (PG) production induced by tensile mechanical forces in bone cells cultured on collagen ribbons. Fetal rat calvaria cells (osteoblast-enriched) were grown on collagen ribbons. The collagen ribbons were stretched under culture conditions in a machine that recorded force and displacement. Repeated stretching of the collagen ribbons (8 times, 5-10%, over 2 hours) increased the rate of prostaglandin synthesis approximately 3.5-fold over that of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
1
1

Year Published

1986
1986
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(54 citation statements)
references
References 19 publications
1
51
1
1
Order By: Relevance
“…As Ca 2þ i mobilization is an early intracellular signalling event involved in bone mechanotransduction, and ALP is a marker for bone mineralization and ECM deposition, these are good indicators of the anabolic effect of mechanical stimulus. Past studies applying large strains (more than 10 000 m1) have also observed increased nitric oxide (NO) and prostaglandin (PG) production, both essential for an osteogenic response, at these strain levels [49,50]. In contrast, more recent studies have suggested that production of NO and PGs, as well as mRNA expression of the important bone remodelling protein osteopontin, may be more closely linked with loading-induced fluid flow than direct substrate stimulation [9,48,51].…”
Section: Discussionmentioning
confidence: 99%
“…As Ca 2þ i mobilization is an early intracellular signalling event involved in bone mechanotransduction, and ALP is a marker for bone mineralization and ECM deposition, these are good indicators of the anabolic effect of mechanical stimulus. Past studies applying large strains (more than 10 000 m1) have also observed increased nitric oxide (NO) and prostaglandin (PG) production, both essential for an osteogenic response, at these strain levels [49,50]. In contrast, more recent studies have suggested that production of NO and PGs, as well as mRNA expression of the important bone remodelling protein osteopontin, may be more closely linked with loading-induced fluid flow than direct substrate stimulation [9,48,51].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the synthesis of prostaglandins by cultured osteoblasts isolated from rat calvaria is increased upon stretching (25). It is not known whether ICF causes mouse chondrocytes (the main body of the cells in a fetal long bone) to increase their synthesis of prostaglandins.…”
Section: Discussionmentioning
confidence: 99%
“…mechanical load (5). The effect of mechanical load on PGE2 synthesis have already been documented (6,7).…”
mentioning
confidence: 93%